A Novel Method for Predicting Residual Stress in GH4169 Machined Surfaces through Micro-Hardness Measurement - Gonghou Yao; Zhanqiang Liu; Haifeng Ma (Applied Sciences, 2023)
The presence of residual stress seriously affects the mechanical performance and reliability of engineering components. Here, the authors propose a novel method to determine corresponding residual stress through micro-hardness measurements of machined surfaces. In this study, a mathematical model with equal biaxial stress indentation is established. Then, the correlation of micro-hardness with indentation and residual stress is used to determine the prediction equation of residual stress. The material applied in this study is the nickel-based Superalloy GH4169. The residual stress prediction formula for Superalloy GH4169 is ultimately determined through the finite element method by subjecting the indentation to residual stress and fitting the experimental test data. The relationship between the indentation modulus and indentation depth is given quantitatively. The relationship between residual stress and hardness is given quantitatively. The prediction results show that the compressive residual stress can enhance the material hardness and make the contact deformation only require a low indentation depth to achieve complete plastic deformation. Conversely, the tensile residual stress can result in a deeper depth and less hardness at the initial stage of the fully plastic state. For the materials that yield more easily (small ratio of elastic modulus to yield strength), the effect is more evident. The model presented in this paper can accurately forecast corresponding residual stress through measurements of the micro-hardness of machined surfaces.